2017
DOI: 10.1371/journal.pone.0172953
|View full text |Cite
|
Sign up to set email alerts
|

The interdependencies of viral load, the innate immune response, and clinical outcome in children presenting to the emergency department with respiratory syncytial virus-associated bronchiolitis

Abstract: Respiratory syncytial virus (RSV) causes significant infant morbidity and mortality. For decades severe RSV-induced disease was thought to result from an uncontrolled host response to viral replication, but recent work suggests that a strong innate immune response early in infection is protective. To shed light on host-virus interactions and the viral determinants of disease, copy numbers of five RSV genes (NS1, NS2, N, G, F) were measured by quantitative real-time polymerase chain reaction (qPCR) in nasal was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 44 publications
3
31
1
1
Order By: Relevance
“…On the other hand, it could also be possible that higher RSV loads promote an early robust innate immune response that can protect from disease progression. Supporting the latter, and in agreement with our findings, a recent study conducted in older infants with RSV infection showed that those with milder disease not requiring hospitalization had higher RSV loads, and that VL was significantly correlated with mucosal concentrations of proinflammatory cytokines [5,20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, it could also be possible that higher RSV loads promote an early robust innate immune response that can protect from disease progression. Supporting the latter, and in agreement with our findings, a recent study conducted in older infants with RSV infection showed that those with milder disease not requiring hospitalization had higher RSV loads, and that VL was significantly correlated with mucosal concentrations of proinflammatory cytokines [5,20].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, steroid use is not mentioned in the majority of studies that have analyzed RSV load dynamics. Although with the current study design it not possible to determine whether steroids are responsible for the slower viral decay, indicative of sicker children, or a combination of both, our study suggests that this is an important cofounding factor [5,6,27] that may have contributed to the differences observed. For these models, we used RSV loads and the CDSS at enrollment.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…On the other hand, a recent publication reported an association between ALRI in children by coronavirus alone or in co-detection with rhinovirus C and severity of the disease, defined as need for admission to the pediatric intensive care unit in our hospital [41]. On regards to viral load, many studies have assessed the role of RSV viral load in predicting worse outcomes, with conflicting results [42]. It has been recently suggested that higher RSV viral loads at presentation elicits a more robust inflammatory response, resulting in faster viral clearance, which could be associated with milder disease [43].…”
Section: Discussionmentioning
confidence: 98%
“…To examine the robustness of the findings, we conducted a series of sensitivity analyses. First, to address potential dilutions of the specimens, we normalized the CCL5 level by using RNase P (host housekeeping gene) copy number, as we have previously described (6). Second, we performed a subgroup analysis excluding patients who had a breathing problem before the index hospitalization.…”
Section: To the Editormentioning
confidence: 99%